Make a Match-Based Instructional Medium for Regional Creation Dance Learning in Elementary Schools - Suci Permata Sari; Rosarina Giyartini; Sumardi Sumardi (Indonesian Journal of Primary Education, 2021)
Teacher competence in teaching and learning process is needed to appropriately deliver learning content so that students and teachers can achieve learning objectives. Teachers experienced obstacles in implementing dance learning in SBdP subject in elementary schools based on interviews and documentation studies. This research aims to develop a puzzle as an instructional medium to assist teachers in overcoming obstacles to the implementation of dance learning. The puzzle development is an effort to assist teachers in overcoming the problems encountered. The puzzle designed by the researchers was combined with the make a match concept (make a pair) so that learning was not only fun, but students could deepen their understanding of the material to be delivered. This study used a design-based research method (DBR) with the Reeves (2006) model. The research began with problem identification, developing a solution prototype, carrying out an iterative process in product testing, and reflection. The product can be used optimally by adjusting the indicators for the development of instructional medium. Researchers obtained suggestions and improvements to the product developed through the validity test phase done by the validator. Based on the validity test results done by the validator and the trial to students, the puzzle design was align with the needs of instructional media and the characteristics of students. Trials to students were carried out twice with positive responses to the use of instructional media. Thus, a decent final product could be produced, namely, puzzle as an instructional medium which was based on make a match concept to help overcome obstacles to the implementation of dance learning in SBdP subject in elementary schools..